Apoptosis and associated phenomena as a determinants of the efficacy of photodynamic therapy. Issue 8 (29th August 2015) - Kessel, David
<x xml:space="preserve">Abstract</x> Failure of neoplastic cells to respond to conventional chemotherapy is usually associated with factors that limit access of drugs to subcellular sites, differences in cell-cycle kinetics or mutations leading to loss of drug-activation pathways or other processes that govern response factors.